ANALISIS PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2023 - Suwantono, Edwin; Indah, Nopiani (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research aims to test whether there is an influence of the independence of capital structure, company size and profitability on company value.  This research provides important implications for energy sector company managers and capital market regulators in determining optimal strategies related to capital structure, asset management, and increasing profitability to increase company value. The research uses panel data with annual data over a period of seven years from 2017-2023. The population in this research is all 90 companies in the Energy Sector of the Indonesia Stock Exchange listed in 2023. The research sample was obtained using a purposive sampling method totaling 27 companies in the Energy Sector of the Indonesia Stock Exchange. The total number of data observations used was 189 data. The research method used is multiple linear regression with Eviews 10. The research results show that company size and profitability have a positive effect on company value. Meanwhile, capital structure has no effect on company value.